Residential Environment Induced Preference Heterogeneity for River Ecosystem Service Improvements: A Comparison between Urban and Rural Households in the Wei River Basin, China - Hengtong Shi; Minjuan Zhao; Fanus Asefaw Aregay; Kai Zhao; Zhide Jiang (Discrete Dynamics in Nature and Society)
This paper assesses residential environment induced preference heterogeneity regarding ecosystem services improvements of a river basin by comparing urban and rural residents’ welfare estimates. In a choice experiment, the ecological improvements are described in terms of several observable ecological indicators set in an experimental design. Given the fact that economic and environmental conditions differ for urban and rural residents in China, the utility they derive from ecological restoration is hypothesized to differ. The urban and rural residents’ survey data were modeled separately using mixed logit models. The results reveal that water quality and water quantity, measured by unit of level improvement and percentage improvement, respectively, hold the highest marginal utility values in all respondents’ models. Urban and rural residents have the same preference regarding expanding soil erosion control areas and landscape improvement. However, they have statistically significant different utility for water quality, water quantity, forest coverage, ecotourism improvements, and reducing soil erosion intensity. Generally, urban residents express a higher implicit price for most of the ecological indicators. The findings imply that policy makers should take existing preference heterogeneity into account in designing ecosystem payment schemes and allocating resources.